An event model for phylogenetic biogeography using explicitly geographical ranges - Arias Becerra, Joan Salvador (2017)
Aim: To develop and implement a method for phylogenetic biogeography that is both event based and geographically explicit, that is, that uses the geographical ranges observed in the terminals instead of ‘predefined areas.’. Methods: The method, GEM (Geographically explicit Event Model), attributes vicariance, sympatry (range copying), point sympatry (subset sympatry) or founder events, to the internal nodes of the tree. The cost of a reconstruction is calculated as the event cost plus the amount of range changes along a branch, and the best reconstruction is the combination of the event and range assignments that minimize the cost. Results: The approach was implemented in a computer program, evs, using a geographical data model (a raster) in which range changes were measured by pixel counts. The program can be used in real-sized datasets, using an heuristic to find reasonable solutions in short times. Main conclusion: GEM provides a method for direct analysis of joint data on phylogeny and explicit distribution ranges, and proposes both the ancestral ranges and the biogeographical events connected with cladogenesis.